標的マーケティングの事例研究 - ヨシダ, ハルオ; 67; 吉田, 春生; Yoshida, Haruo (鹿児島国際大学福祉社会学部, 2012)
application/pdf 観光マーケティングにおける成功例は少なからずある。もちろん、それにも増して多くの失敗例もある。この論考ではマス・マーケティングではなく、標的マーケティングについて取り上げる。異色の旅行目的地は、「オフ・ザ・ピートン・トラック」を好みそれに高額な料金を払ってもよいという顧客には魅力的である。例えば、南極旅行やエベレスト営業登山、ホテル･エベレスト・ビューである。これらは標的マーケティングの典型的な事例であるが，観光という社会現象における問題点もそこには早まれており、注意を要する。 There are many successful examples in tourism marketing. Of course, more examples were unsuccessful in sales promotion. In this paper I make reference to target marketing, not to mass marketing. An unique destination attracts guests who like "off the beaten track" and pay higher costs for it. For example, a tour to the South Pole, commercial climbing Mt. Everest, and staying at Hotel Everest View. 論文(Article) departmental bulletin paper